The Dilemma of Handling Asylum Seekers and Illegal Migrants: Expectation and Reality - Marten Hanura; Reni Windiani; Tri Cahyo Utomo (Andalas Journal of International Studies (AJIS), 2021)
The number of refugees and illegal migrants fleeing to Indonesia keeps growing significantly since Indonesia poses as a strategic place for a temporary stop before their main destination. This surely brings about predicaments to Indonesia. Against that background, this research aims toanswer the question of "How does the Indonesian government respond to the illegal migrant and refugees problem through the Immigration Detention Center (Rudenim) Semarang in Central Java?". This research is an explanatory research, where both primary and secondary data are used to support the findings. Through a qualitative approach, this research foundthat the government has responded to illegal migrant and refugees problems in a quite excellent manner such as the establishment of rumah detensi imigrasi (rudenim) or detention house and other forms of international cooperation. However, asylum seekers in Indonesia are not fully protected due to some factors such as the lack of regulation, the long-waiting period for the permanent placement and the lack of basic needs.Lastly, the situation only got worse because of the IOM and UNHCR support is still not optimal.